2018
DOI: 10.20319/pijss.2018.42.453465
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Mental Health of Undergradute Students at a Private Higher Learning Institution in Malaysia

Abstract: Malaysia has an uprising trend in mental health problem among tertiary level students based on statistics which shows there is an increase in the number cases registered from 2011 to 2016.Mental health problems among students are caused by anxiety and also depression and at same time the influence of drugs as a factor is also a possible plausible cause. Hence, this study was aimed to seek some confirmations to the statement and determine the overall state of the students' mental health. Apart from that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Medical students are relatively younger in private institution than in public university. College life for teenagers may impose major challenges to studying and socializing and failure to manage these challenges may lead to poor mental health with repercussions [ 36 ]. Private universities have stricter rules, restriction of movement and freedom and stiffer punishments for disobedience.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students are relatively younger in private institution than in public university. College life for teenagers may impose major challenges to studying and socializing and failure to manage these challenges may lead to poor mental health with repercussions [ 36 ]. Private universities have stricter rules, restriction of movement and freedom and stiffer punishments for disobedience.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the top leading factors contributed to overall student academic stress were dealing with difficult subjects through online learning in addition to multiple assignments and submission deadlines. A study found that the majority of the Malaysian students were unprepared with the sudden leap to e-learning which has adversely affected their self-confidence and motivation, causing the worsening of stress level [14] . Besides the transition to online classes, next biggest perceived challenge was the quality of the classes which was conducted online make the difficulty in learning and understanding [9] .…”
Section: Discussionmentioning
confidence: 99%
“…The score was added up with a cumulative score of 40. Each student was categorized into mild (10)(11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and severe stress (30-40). The validity has been tested by a panel of experts with Cronbach's α = 0.842.…”
Section: Study Instrumentmentioning
confidence: 99%
“…These stressors and challenges may impair their learning capacity and academic achievement (Balaji et al, 2019;Gedam et al, 2020;Sridar, 2018). Academic factors (Bisai & Chaudhary, 2017;Gedam et al, 2020;Navarro-Martínez et al, 2020;Reddy et al, 2018;Sridar, 2018) and financial problems (Othman & Rashid, 2018;Negi et al, 2019;Reta et al, 2020;Gedam et al, 2020) have been identified to be the most frequent sources of stress for university students. Other than these common stressors, environmental factors, interpersonal relationships (Balaji et al, 2019), financial management issues, shifts in the living environment such as staying away from family, and challenges balancing personal and academic life also causes stress to university students (Navarro-Martínez et al, 2020;Reddy et al, 2018).…”
Section: 10 Introductionmentioning
confidence: 99%
“…Different fields or courses taken in the university have been reported to have different levels of stress among university students (Othman & Rashid, 2018). It may be due to the different subjects and difficulty levels that are exposed to and learned by university students depending on their courses.…”
Section: 10 Introductionmentioning
confidence: 99%